Direct amination of γ-halo-β-ketoesters with anilines - Zhang, Yinan (2012)
[Image: see text] The direct amination of α-haloacetoacetates with anilines is described. Compared to existing methods, this simple protocol provides an attractive strategy to prepare diverse γ-anilino-β-ketoesters in one step. Good to excellent yields of the amination products were obtained under robust conditions, providing versatile and useful scaffolds.